Speech Acts In Sibt Ibn Al-Ta'awidhi's Poem: A Pragmatic Study/ الفعل الكلامي في رائية سبط ابن التعاويذي: دراسة تداولية - Salah Mohsin Hazim (Ijaz Arabi Journal of Arabic Learning, 2026)
This research aims to uncover the pragmatic dimensions of Ibn Sibt al-Ta'awidhi's (d. 584 AH) ode by analyzing its speech acts as linguistic components that perform performative functions extending beyond verbal structure to the intended effect on the recipient. The study is based on the pragmatic approach as a theoretical framework, drawing on speech act theory as formulated by Austin and Searle, and its representational, directive, expressive, obligatory, and declarative classifications, to reveal how the poet employs poetic language to perform acts of influence, persuasion, and rapprochement with authority. It also utilizes modern concepts linking language and social context, such as those of Grice and Bourdieu, highlighting the relationship between poetic utterance and the requirements of the situation and symbolic hegemony. The research concludes that Ibn Sibt al-Ta'awidhi's ode is a significant model of the intersection of poetry and pragmatics, as the speech acts within it vary according to the poet's intentions and the functions of the discourse. The representative acts establish praise as a discourse of truth and loyalty, while the directive acts work to win over the recipient and convince him of the legitimacy of the Caliph. As for the expressive acts, they reveal the sincere emotion and emotional belonging, while the obligatory and advertising acts are responsible for consolidating the image of the poet committed to serving the Sultan.